Physical link of the polar field buildup with the Waldmeier effect broadens the scope of early solar cycle prediction: Cycle 25 is likely to be slightly stronger than Cycle 24 - Kumar, Pawan; Biswas, Akash; Karak, Bidya Binay (Oxford University Press, 2022)
Prediction of the solar cycle is challenging but essential because it drives space weather. Several predictions with varying amplitudes of the ongoing Cycle 25 have been made. We show that an aspect of the Waldmeier effect (WE2), i.e. a strong positive correlation between the rise rate and the amplitude of the cycle, has a physical link with the buildup of the previous cycle's polar field after its reversal. We find that the rise rate of the polar field is highly correlated with the rise rate and the amplitude of the next solar cycle. Thus, the prediction of the amplitude of the solar cycle can be made just a few years after the reversal of the previous cycle's polar field, thereby extending the scope of the solar cycle prediction to much earlier than the usual time. Our prediction of Cycle 25 based on the rise rate of the previous polar field is 137 ± 23, which is quite close to the prediction 138 ± 26 based on the WE2 computed from the available 2 yr sunspot data of the ongoing cycle.
This paper is submitted by the author of IIT (BHU), Varanasi
Keywords: activity; dynamo; magnetic fields; Sun; sunspots